A Comparator-Less Buck Converter with Fast Transient Response Using a Reactive Ramp Generator - Young-Kyu Kim; Chung-Hee Jang; Dong-Hyun Shin; Kwang-Hyun Baek (Energies)
This paper introduces a voltage-mode DC-DC buck converter designed to address the challenges of high-frequency operation. The proposed comparator-less Reactive Ramp Generator (RRG) topology mitigates the issues associated with comparator delays, achieving a fast load transient response. By eliminating all comparators from the buck converter’s control circuit, we prevent potential delay-induced malfunctions, thereby enhancing overall operational reliability. The rapid response of the RRG, enabled by a short feedback loop, allows for swift output voltage regulation during load transients. Replacing comparators in the PWM controller with inverters effectively removes delay issues without adding complexity. Since the proposed design retains the conventional voltage-mode transfer function, standard type-3 compensation is readily applicable. Operating with a 3.3 V input, the buck converter provides an output range from 0.65 V to 3.0 V, achieving a settling time of 0.802 µs for load changes from 200 mA to 1 A, and 1.27 µs for load changes from 1 A to 200 mA. The proposed architecture achieves a peak efficiency of 92.78% at 2.4 V and 600 mA.